2020
DOI: 10.4018/978-1-5225-9902-9.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Disease Identification in Plant Leaf Using Deep Convolutional Neural Networks

Abstract: Early detection of disease in the plant leads to an early treatment and reduction in the economic loss considerably. Recent development has introduced deep learning based convolutional neural network for detecting the diseases in the images accurately using image classification techniques. In the chapter, CNN is supplied with the input image. In each convolutional layer of CNN, features are extracted and are transferred to the next pooling layer. Finally, all the features which are extracted from convolution l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Guo et al [8] reported accuracy rates of 94.0 percent, 86.7 percent, 88.8 percent, and 84.4 percent, respectively, for the identification of downy mildew, anthracnose, powdery, and grey mould infections. Venu et al [9] developed a neural network-based pattern recognition method to pinpoint the most common tomato late blight disease on a global scale. In the present approach of 20 networks, the best prediction level for pixel classification was 97.99 percent.…”
Section: Ai Based Phenomics Approach In Disease Identificationmentioning
confidence: 99%
“…Guo et al [8] reported accuracy rates of 94.0 percent, 86.7 percent, 88.8 percent, and 84.4 percent, respectively, for the identification of downy mildew, anthracnose, powdery, and grey mould infections. Venu et al [9] developed a neural network-based pattern recognition method to pinpoint the most common tomato late blight disease on a global scale. In the present approach of 20 networks, the best prediction level for pixel classification was 97.99 percent.…”
Section: Ai Based Phenomics Approach In Disease Identificationmentioning
confidence: 99%
“…The algorithm inspired by the diverse structure of the human brain; the Artificial Neural Network (ANN) has been used in numerous complex problems [7]. It can process a large volume of data, learn from training data, and excellent generalization capability [8]. Due to its capability of self-learning and self-adapting, more research on this algorithm has been successfully implemented to solve real-world problems.…”
Section: Introductionmentioning
confidence: 99%
“…The Artificial Neural Network (ANN) has the ability to learn from experiences, improving its performance and adapting to the changes in the environment [2]. The key benefits of neural networks are the prospect of processing vast quantities of data effectively, and their ability to generalize outcomes [3]. The ANNs are parallel distributed systems, consisting of simple processing units (artificial neurons) that measure with certain (usually nonlinear) [4] mathematical functions.…”
Section: Introductionmentioning
confidence: 99%